Strategic Human Resource Management Practices as Antecedents of Employee Corporate Entrepreneurial Intensity - Jose Rommel Era (SEISENSE Business Review)
This study investigates the influence of training, performance appraisal, and rewards (SHRMPs) on corporate entrepreneurial intensity (CEI) in a Philippine medium-sized fintech firm and examines the moderating role of organizational culture (OC). Data from 68 managerial employees were analyzed using linear regression and moderation analysis. Results show SHRMPs significantly impact CEI, with OC notably moderating this relationship, particularly for training. These findings offer guidelines for SMEs in emerging economies on designing HR programs to foster CEI, emphasizing the critical role of a supportive organizational culture. This study fills a gap by focusing on an SME in an emerging economy and highlighting OC's moderating effect.